Analysis of Publising Business Competitive Strategies with Method SWOT - Azizah, Fitria Nurul; Meisaroh, Laela (Islamic Studies Journal, 2023)
Business Publishing is business Which most in obsessed by public general, in side many student And student Which requires books as a reference, this business also has a large profit margin relatively large. As technology develops, promotion becomes easier make this business have many competitors. Creative House Publishers Wadas Kelir is a business that operates in the publishing and publishing sector has many competitors, each of which has its own way of doing things attract consumers. Wadas Kelir Creative House publisher is able to compete with its competitors to date even though the business location is less strategic and classified Still new However own value separately in the eyes consumer. So that For still maintain his business And increase turnover very required strategy compete Which appropriate And can recognize the environment. In this research, the analytical tool used is Analysis SWOT to determine the right strategy through the external environment and internal industry. The main aim of this research is to analyze what strategies are has been implemented by Wadas Kelir Creative House Publishers and provides an alternative strategies that suit the company's position and circumstances. This type of research namely field research (Field Research) with a qualitative approach. Source The data used are primary data sources, namely interviews and observations as well as secondary i.e document sales, photos, document Which has something to do with study. Technique collection data on research This use technique observation participation, interview deep And documentation. Data processed use tool analysis SWOT For know strength, weakness, opportunities and threats from the company which are then analyzed to compile strategy competing ones right on Publisher Creative Home Wadas Color. The research results obtained are that the competitive strategy of the publishing business Rumah Creative Wadas Kelir applied is a cost leadership strategy, differentiation strategy and focus strategy. Then through the SWOT matrix, strategy which is appropriate to be applied to the Wadas Kelir Creative House Publisher in the future now and in the future is a WO strategy by utilizing opportunity which exists For repair as well reduce weakness which exists.